High resolution upgrade of the ATF damping ring BPM system - Terunuma, N; Urakawa, J; Frisch, J; May, J; McCormick, D; Nelson, J; Seryi, A; Smith, T; Woodley, M; Briegel, C; Dysert, R; Eddy, N; et al. (2008)
A beam position monitor (BPM) upgrade at the KEK Accelerator Test Facility (ATF) damping ring has been accomplished in its first stage, carried out by a KEK/FNAL/SLAC collaboration under the umbrella of the global ILC RandD effort. The upgrade consists of a high resolution, high reproducibility read-out system, based on analog and digital donwconversion techniques, digital signal processing, and also tests a new automatic gain error correction schema. The technical concept and realization, as well as preliminary results of beam studies are presented.